2014
DOI: 10.18632/oncotarget.2694
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of zoledronic-acid resistant prostate cancer cells unveils novel pathways characterizing an invasive phenotype

Abstract: Proteomic analysis identified differentially expressed proteins between zoledronic acid-resistant and aggressive DU145R80 prostate cancer (PCa) cells and their parental DU145 cells. Ingenuity Pathway Analysis (IPA) showed a strong relationship between the identified proteins within a network associated with cancer and with homogeneous cellular functions prevalently related with regulation of cell organization, movement and consistent with the smaller and reduced cell-cell contact morphology of DU145R80 cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 51 publications
(66 reference statements)
5
30
0
Order By: Relevance
“…1-D Western blotting results showed that differently from DU145, DU145R80 cells had undetectable E-cadherin and high vimentin, MMP-2 and MMP-9 expression (Figure 5A ) confirming our previous observations [ 9 , 10 ]. As also reported before, confocal microscopy analyses showed that DU145 cells were characterized by a more epithelial-like morphology: in these cells F-actin staining showed a well organized cytoskeleton with the appearance of several cortical stress fibers (Figure 5B, panel b ; arrows), suggesting a less motile phenotype.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…1-D Western blotting results showed that differently from DU145, DU145R80 cells had undetectable E-cadherin and high vimentin, MMP-2 and MMP-9 expression (Figure 5A ) confirming our previous observations [ 9 , 10 ]. As also reported before, confocal microscopy analyses showed that DU145 cells were characterized by a more epithelial-like morphology: in these cells F-actin staining showed a well organized cytoskeleton with the appearance of several cortical stress fibers (Figure 5B, panel b ; arrows), suggesting a less motile phenotype.…”
Section: Resultssupporting
confidence: 89%
“…By using a 2-DE DIGE proteomic approach, we show that ANXA1 is up-regulated in DU145R80 ZA-resistant PCa cells compared with their parental DU145 cells [ 10 ]. Thus, we first evaluated the role of ANXA1 in the maintenance of drug resistance to ZA in DU145R80 PCa cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to catalysing aldehyde metabolism, ALDH7A1 also plays a role in protecting tissues from the damaging effects of osmotic stress [89] while mutation of the ALDH7A1 gene has been related to pyridoxinedependent epilepsy [90,91] . In cancer, ALDH7A1 is expressed in nodular melanoma (NM) [92] , ovarian [93] and lung cancers [94] while in PCa the isoform has been shown to be involved in intra-bone growth and induced bone metastasis [64] as well as zoledronic acid resistance [95] . Gene expression profiling supports the involvement of ALDH7A1 in multiple molecular pathways related to the metastatic process in PCa [96] .…”
Section: Aldh Expression and Regulation In Prostate Cancermentioning
confidence: 99%